2022
DOI: 10.1177/00219983221111493
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the properties of Alfa/wool woven fabrics reinforced epoxy composite as an application in wind turbine blades

Abstract: Wind energy is the kinetic energy of wind transformed into electrical energy by a system known as a wind turbine. All of the different parts of a wind turbine, like blades, hub, gearbox, nacelle, and tower, blades are usually made of glass and carbon fibers for better strength, lower weight, and better resistance to corrosion. The main limitations of these materials are the availability, non-biodegradable, health hazards, and fabrication cost. The development of interwoven fabric based on natural fiber for com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Upon closer scrutiny of the 467 examined documents, only a few studies revealed composites designed explicitly for targeted applications, as outlined in Table 3. Additionally, other studies explored the development of composites for potential applications, including wind turbine blades, 36,37 automobile body parts, [38][39][40] ballistic armour components, 41,42 non-structural building panels, 43,44 pressure vessels, 45 electric circuit boards, 46 and composite film for packaging applications. 47,48…”
Section: Publication Outputmentioning
confidence: 99%
“…Upon closer scrutiny of the 467 examined documents, only a few studies revealed composites designed explicitly for targeted applications, as outlined in Table 3. Additionally, other studies explored the development of composites for potential applications, including wind turbine blades, 36,37 automobile body parts, [38][39][40] ballistic armour components, 41,42 non-structural building panels, 43,44 pressure vessels, 45 electric circuit boards, 46 and composite film for packaging applications. 47,48…”
Section: Publication Outputmentioning
confidence: 99%
“…E-glass/epoxy composites are ideal for use in small-to-medium-sized wind blades. S-glass/epoxy composites which are made of S-glass fibres can also be used in the wind blade manufacturing [41]. This type of S-glass fibre is much more durable and rigid than E-glass fibre and has an increased tensile strength and modulus.…”
Section: Literature Surveymentioning
confidence: 99%
“…The flax fibre employed in this study shares the same drawback as any other natural fibre with a hydrophilic character [48]. Figure 4 shows the weight comparison of micro-size HAWT blades manufactured from the mentioned composites, where it is apparently evident how lightweight flax-based composites are [41][42][43]45].…”
Section: Literature Surveymentioning
confidence: 99%
“…The development of fabrics based on natural fibers for the production of composites is a new technology that can solve the challenge of balanced mechanical properties of composites. In the work of Lamhour et al [19], alfa and wool fibers were used as reinforcement for the development of four fabrics and low viscosity unsaturated epoxy resin as matrix. The fabrics were fabricated applying the taffeta weaving technique.…”
Section: Wind Turbine Bladesmentioning
confidence: 99%